Essential Oils in Respiratory Mycosis: A Review - Mónica Zuzarte; Lígia Salgueiro (Molecules, 2022)
Respiratory mycosis is a major health concern, due to the expanding population of immunosuppressed and immunocompromised patients and the increasing resistance to conventional antifungals and their undesired side-effects, thus justifying the development of new therapeutic strategies. Plant metabolites, namely essential oils, represent promising preventive/therapeutic strategies due to their widely reported antifungal potential. However, regarding fungal infections of the respiratory tract, information is disperse and no updated compilation on current knowledge is available. Therefore, the present review aims to gather and systematize relevant information on the antifungal effects of several essential oils and volatile compounds against the main type of respiratory mycosis that impact health care systems. Particular attention is paid to Aspergillus fumigatus, the main pathogen involved in aspergillosis, Candida auris, currently emerging as a major pathogen in certain parts of the world, and Cryptococcus neoformans, one of the main pathogens involved in pulmonary cryptococcosis. Furthermore, the main mechanisms of action underlying essential oils’ antifungal effects and current limitations in clinical translation are presented. Overall, essential oils rich in phenolic compounds seem to be very effective but clinical translation requires more comprehensive in vivo studies and human trials to assess the efficacy and tolerability of these compounds in respiratory mycosis.